2014
DOI: 10.1021/ef401903y
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Simulations of Steady Perforated-Plate Stabilized Propane–Air Premixed Flames

Abstract: A numerical investigation of steady laminar premixed propane−air flames is presented. A three-dimensional simulation has been performed to examine the impact of operating conditions on steady-state characteristics of a perforated burner flame. A numerical simulation has been carried out using a reduced propane−air reaction mechanism having 30 species and 192 reactions. The results are validated against the one-dimensional flat-flame result obtained using PREMIX. Effects of the equivalence ratio, inlet velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Jithin et al 17 examined the influence of operating conditions of a premixed laminar flame on steady-state characteristics of a perforated-plate burner. They reported that increasing the inlet velocity increases the stand-off distance of the flame, whereas increasing the equivalence ratio increases the plate heat flux as the flame goes nearer to the plate.…”
Section: Introductionmentioning
confidence: 99%
“…Jithin et al 17 examined the influence of operating conditions of a premixed laminar flame on steady-state characteristics of a perforated-plate burner. They reported that increasing the inlet velocity increases the stand-off distance of the flame, whereas increasing the equivalence ratio increases the plate heat flux as the flame goes nearer to the plate.…”
Section: Introductionmentioning
confidence: 99%
“…Such large mechanisms need to be reduced for computationally tractable threedimensional (3-D) simulations. Reduced mechanisms for propane have been developed from detailed chemistry [26,27,28,29], and employed successfully for Reynold-Averaged CFD simulations [28,29]. For example, Jithin et al [29] have performed a three-dimensional simulation to investigate steady laminar premixed propane-air flames using a reduced mechanism with 30 species and 192 reactions.…”
Section: Introductionmentioning
confidence: 99%
“…They have reported higher flame lift-off as well as strong recirculation for larger hole spacing. Considering laminar air combustion on a PPB, Jithin et al 66 have discovered that the flame stand-off distance increases with larger hole spacing. Hindasageri et al 67 have carried out experiments and numerical investigations of the distribution of heat flux from a multi-hole burner holding CH 4 −air flames, considering different hole arrangements at a low Reynolds number (Re).…”
Section: Existing Burner Technologies In Lpm Gasmentioning
confidence: 99%